Self Management and its Relationship to Anxiety Performance among Trainee Counselors in Jordan. - Althwabeiah, Eman; Tannous , Adel (Dirasat: Educational Sciences, 2021)
The present study aimed to identify the level of self-management and its relationship to performance anxiety in a sample of trained mentors in Jordan. The study sample consisted of (70) male and female students, where the number of male field training students in psychological and educational counseling, and the number of female 59 at the University of Jordan, were selected intentionally. To achieve the objectives of the study, measures of self-management and performance anxiety were developed. The results of the study indicated that the level of self-management among the mentors trained at the University of Jordan came at a "low" level, and the level of performance anxiety among the mentors trained at the University of Jordan came at a "high" level. The study showed a statistically significant negative (inverse) relationship between the level of self-management as a whole among the mentors trained at the University of Jordan and their level of performance anxiety.